Analysis of the Values of Shadow Puppet Art in Strengthening the Code of Ethics for Accountants - Sintia Nur Afifah; Mariska Nur Hanifah; Fitria Auldri; Hudri Ahmad Hudori; Asep Alfarizi Yulianto; Muhammad Aras Prabowo; Fitriah Ulfah; Lusiana Putri Ahmadi (Innovation Business Management and Accounting Journal, 2024)
This research is a literacy study (literature review study) which is a description of several theories, evidence, and other research from various sources (Hasibuan, 2007). The data analysis method is also used in this research, which is descriptive analysis with stages of accumulating data from various previous studies, both national and international research, analyzing the information, and then providing explanations and descriptions of Javanese cultural values, one of which is shadow puppet culture which can function as reinforcement. Accountant's code of ethics. The results of this research show that the Code of Ethics for Accountants adopted from Western culture cannot solve problems in Indonesia. Therefore, the accounting profession currently in Indonesia must understand that foreign culture is very different from the ethical rules that can be adapted to the ethical principles of accountants in Indonesia. Community culture is considered more appropriate for implementing the code of ethics in Indonesia and can be the basis for proposals for developing ethical accounting principles based on local culture, one of which is shadow puppetry.